2018
DOI: 10.15406/iratj.2018.04.00090
|View full text |Cite
|
Sign up to set email alerts
|

Resampling Imbalanced Class and the Effectiveness of Feature Selection Methods for Heart Failure Dataset

Abstract: The real dataset has many shortcomings that pose challenges to machine learning. High dimensional and imbalanced class prevalence is two important challenges. Hence, the classification of data is negatively impacted by imbalanced data, and high dimensional could create suboptimal performance of the classifier. In this paper, we explore and analyse different feature selection methods for a clinical dataset that suffers from high dimensional and imbalance data. The aim of this paper is to investigate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
(25 reference statements)
0
25
0
1
Order By: Relevance
“…The resample has improved classification performance significantly, even on highdimensional data without using the feature selection method in line with previous studies. This previous research has shown that the feature selection methods' role, except for the information gain, is still lesser than the resample method to improve the classification performance, including accuracy, sensitivity, and precision [20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The resample has improved classification performance significantly, even on highdimensional data without using the feature selection method in line with previous studies. This previous research has shown that the feature selection methods' role, except for the information gain, is still lesser than the resample method to improve the classification performance, including accuracy, sensitivity, and precision [20].…”
Section: Resultsmentioning
confidence: 99%
“…SMOTE can obscure the information of data interrelations in every class, thereby reducing the k-NN performance. As in previous studies, the information of interrelation data can be obscured due to the addition of unique samples that lead to generalization errors in the classifier [10], [18], [20]. Because of this flaw, SMOTE needs to be developed as in previous studies to improve the interclass boundary [10], [14], [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kelas yang memiliki banyak instance disebut kelas mayoritas dan yang memiliki jumlah instance yang lebih sedikit disebut kelas minoritas [10]. Dalam situasi kehidupan nyata kadang-kadang kelas minoritas lebih menarik daripada kelas mayoritas, misal dalam data medis pada kasus gagal jantung [11] bidang ekonomi seperti credit scoring [12], credit cards fraud, dimana penyalahgunaan kartu kredit lebih sedikit daripada yang tidak disalah gunakan. serta bidang-bidang lain seperti deteksi spam pada email dimana email berupa spam lebih sedikit daripada bukan spam.…”
Section: Machine Learning (Ml) Merupakan Sub Bidang Dariunclassified